2005
DOI: 10.1111/j.1471-0528.2005.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of severe pre‐eclampsia/eclampsia in Yorkshire 1999/2003

Abstract: On behalf of the Yorkshire Obstetric Critical Care GroupObjective To establish the risk of serious complications from severe pre-eclampsia and eclampsia in a region using a common guideline for the management of these conditions. Design A five-year prospective study.Setting Sixteen maternity units in Yorkshire.Population All women managed with severe pre-eclampsia and eclampsia.Methods A common guideline was developed for the management of women with these conditions. A network of midwives prospectively collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
5
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(122 citation statements)
references
References 16 publications
6
102
5
9
Order By: Relevance
“…10 Tufnell et al reported as high as 72% caesarean section rate in BJOG. 12 Caesarean section rates of 71% and 78% respectively were reported by Miguel M et al and Dissanayake VH et al 13,14 The high rate of caesarean section in the present study is due to more than 36 % cases being previous caesarean section and also due to emergency delivery approach taken to prevent further maternal and fetal complications due to severe preeclampsia or eclampsia especially in cases where the cervix is unfavourable for induction.…”
mentioning
confidence: 55%
“…10 Tufnell et al reported as high as 72% caesarean section rate in BJOG. 12 Caesarean section rates of 71% and 78% respectively were reported by Miguel M et al and Dissanayake VH et al 13,14 The high rate of caesarean section in the present study is due to more than 36 % cases being previous caesarean section and also due to emergency delivery approach taken to prevent further maternal and fetal complications due to severe preeclampsia or eclampsia especially in cases where the cervix is unfavourable for induction.…”
mentioning
confidence: 55%
“…The frequency of placental lesions [15,52,53], as is the frequency of multisystemic involvement [54][55][56][57], is higher in these patients than those who are diagnosed later. For example, hemolysis, elevated liver enzymes, low platelet (HELLP) syndrome is more common in patients with early-onset disease than in those diagnosed at term [58][59][60].…”
Section: Introductionmentioning
confidence: 92%
“…The increased perinatal morbidity associated with preeclampsia is also closely linked to early-onset disease because indicated preterm delivery is associated with an increased risk of neonatal complications [61]. Late-onset disease is, however, much more common than early-onset preeclampsia [56,57,62].…”
Section: Introductionmentioning
confidence: 99%
“…Oral labetalol (200 mg) has been used with good effect within a regional pre-eclampsia protocol [325]. In a clinical trial of preterm severe hypertension, 100 mg of oral labetalol every 6 h achieved the stated BP goal (of about 140/ 90 mmHg) in 47% of women [326].…”
Section: Antihypertensive Therapymentioning
confidence: 99%
“…[314]. The phrase, ''planned delivery on the best day in the best way,'' reflects the myriad of considerations regarding timing (and mode) of delivery [325]. Timing delivery will reflect evolving adverse conditions ( Table 2).…”
Section: Timing Of Delivery Recommendationsmentioning
confidence: 99%